The blood-stage malaria antigen PfRH5 is susceptible to vaccine-inducible cross-strain neutralizing antibody. - Douglas, A; Williams, A; Illingworth, J; Kamuyu, G; Biswas, S; Goodman, A; Wyllie, D; Crosnier, C; Miura, K; Wright, G; Long, C; Osier, F; et al. (2011)
Current vaccine strategies against the asexual blood stage of Plasmodium falciparum are mostly focused on well-studied merozoite antigens that induce immune responses after natural exposure, but have yet to induce robust protection in any clinical trial. Here we compare human-compatible viral-vectored vaccines targeting ten different blood-stage antigens. We show that the full-length P. falciparum reticulocyte-binding protein homologue 5 (PfRH5) is highly susceptible to cross-strain neutralizing vaccine-induced antibodies, out-performing all other antigens delivered by the same vaccine platform. We find that, despite being susceptible to antibody, PfRH5 is unlikely to be under substantial immune selection pressure; there is minimal acquisition of anti-PfRH5 IgG antibodies in malaria-exposed Kenyans. These data challenge the widespread beliefs that any merozoite antigen that is highly susceptible to immune attack would be subject to significant levels of antigenic polymorphism, and that erythrocyte invasion by P. falciparum is a degenerate process involving a series of parallel redundant pathways.